Middle School Teachers' Usage of Dynamic Mathematics Learning Environments as Cognitive Instructional Tools - Escuder, Ana (ProQuest LLC, 2013)
This study described, analyzed, and compared the internal and external factors that prevented or fostered the implementation of a cognitive tool, GeoGebra, in the mathematics practices of 12 middle school teachers who had completed a master's degree program in mathematics successfully. Through the application of a case study approach as a systematic method for the analysis of qualitative data, and under a social constructivist framework, the study examined different factors such as concerns of teachers; their beliefs about technology, mathematics as a subject, math teaching, and learning; external factors such as resources and school support; their TPACK development; and their instrumental orchestration approach through classroom observations. Among the major findings, the study revealed that the personal concerns of the teacher users of GeoGebra included the desire to continue learning the new features of the software, as well as the desire to connect themselves with others in common endeavors for the benefit of other teachers and, ultimately, the students. The external factors such as lack of working computers did not impede but restricted their use of GeoGebra in the classroom. There was a consensus among the teacher users that they had to strike a balance between their professional goals and the available resources. The users expressed feelings of accomplishment as professionals and had been recognized as such by the several awards they received. They did not over-emphasize the challenges they encountered, instead downplaying them with the result of engaging students and providing them with the best learning experiences they could. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]